Cover Picture: Elucidating the Neurotoxicity of the Star Fruit (Angew. Chem. Int. Ed. 49/2013). Issue 49 (7th November 2013) - Garcia‐Cairasco, Norberto; Moyses‐Neto, Miguel; Del Vecchio, Flavio; Oliveira, José A. C.; dos Santos, Francisco L.; Castro, Olagide W.; Arisi, Gabriel M.; Dantas, Márcio; Carolino, Ruither O. G.; Coutinho‐Netto, Joaquim; Dagostin, Andre L. A.; Rodrigues, Marcelo C. A.; et al.
<x xml:space="preserve">Abstract</x> The potent and deadly neurotoxin caramboxin was extracted from star fruits, as N. Garcia‐Cairasco, N. P. Lopes, et al. describe in their Communication on page 13067 ff. The main targets of caramboxin intoxication are the kidney and the brain. A worldwide awareness is needed for thousands of people who are exposed to this new phenylalanine‐like neurotoxin. (Cover by N. Garcia‐Cairasco)<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>